1997
DOI: 10.1080/13583149708047675
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Nematic Liquid Crystal Droplets

Abstract: iquid crystal droplets, being L relatively easy to produce, have been of interest since the early days of liquid crystals. This interest is both scientific and practical. Scientifically, we would like to know how confinement can alter the macroscopic properties of materials previously understood only in the bulk. In the case of liquid crystal droplets, the boundary conditions are fundamentally incompatible with parallel orientation in the bulk, which leads to topological defects in the structure. By applying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…2. Идеализированное представление композитов с разной ориентацией ЖК-директора в каплях холестерика с различными граничными условиями: а -Frank-Pryce текстура в случае тангенциальных граничных условий ориентации [10], b -случай с гомеотропными или радиальными граничными условиями [11], c -случай, изображенный на b -в условиях одноосного растяжения. 1 -капля жидкого кристалла с холестерическими «слоями», 2 -полимерная сшитая матрица Fig.…”
unclassified
See 1 more Smart Citation
“…2. Идеализированное представление композитов с разной ориентацией ЖК-директора в каплях холестерика с различными граничными условиями: а -Frank-Pryce текстура в случае тангенциальных граничных условий ориентации [10], b -случай с гомеотропными или радиальными граничными условиями [11], c -случай, изображенный на b -в условиях одноосного растяжения. 1 -капля жидкого кристалла с холестерическими «слоями», 2 -полимерная сшитая матрица Fig.…”
unclassified
“…2. An idealized representation of composites with different orientations of the LC director in cholesteric droplets at different boundary conditions: a -Frank-Pryce texture in the case of tangential boundary conditions of orientation [10], b -the case with homeotropic or radial boundary conditions [11], c -the case shown in b -under uniaxial tension.…”
mentioning
confidence: 99%
“…(b) A CLC with a visible long pitch p 0 (order of mm, but significantly less than the droplet radius) initially shows a Frank-Pryce texture, with the helical axis oriented normal to the droplet surface, creating a characteristic''bull's eye'' owing to the pseudolayering created by the helical modulation of the LC. 37,39,40 In presence of 1 mM SDS, the droplet switches to a ''fingerprint'' texture where the helical axis instead sits tangentially along the droplet interface. 41,42 (c) For CLCs with short pitches, comparable to the wavelength of visible light, the responses are manifested in colors in the form of a characteristic ''starburst'' associated with the Frank-Pryce texture and cross-droplet communication 18,37,43 to form a multidomain, diffuse, ''chicken-skin'' pattern 18,23 associated with the degeneracy of the CLC helix axis orientation at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…For the films produced in the present study, a Maltese cross, indicative of radial alignment, was observed during each birefringence experiment for the 40, 70, and 120 nm thick CNC films (Figure ). The observation of a Maltese cross indicates a symmetry between the particles; however, this characterization cannot identify if the film has radial or a Frank–Pryce structure . Here, the presence of symmetry observed through birefringence is used as evidence of structure.…”
Section: Resultsmentioning
confidence: 99%
“…The observation of a Maltese cross indicates a symmetry between the particles; however, this characterization cannot identify if the film has radial or a Frank−Pryce structure. 36 Here, the presence of symmetry observed through birefringence is used as evidence of structure. The local variation in the moduli and its agreement with CG-MD results provide further evidence of radial alignment.…”
Section: Resultsmentioning
confidence: 99%